Theme restaurants in North Lima: Value chains and initiatives to strengthen them - Torres-Castillo , Aníbal (2023)
The purpose of the research is to understand the operation of the theme restaurant value chains in North Lima, which facilitate the identification of initiatives for their strengthening. Knowing what happens in the links of the value chain makes it possible, from a holistic perspective, to have control of the key success factors in running these restaurants. The research was carried out with a qualitative approach, taking into account the research design based on the multiple case study, which is characterized by focusing on one or more cases and the contexts that surround it, to later determine through triangulation, patterns of concurrence, differences, limitations or occurrences, consistent with the a priori and emerging categories that emerge from the purpose of the research. Three restaurants participated, which were visited on more than one occasion and the semi-structured conversational interview was used as a method for collecting information, and observation as a complementary method. It is concluded that in the three links that make up the value chain, there are key processes that add value to the efficiency and operability of restaurants and that in practice are key success factors and that control must be exercised.